2015
DOI: 10.1111/jicd.12180
|View full text |Cite
|
Sign up to set email alerts
|

Betel quid oral lichenoid lesions: a hospital based cross‐sectional study

Abstract: The prevalence of betel quid oral lichenoid lesions was higher than that reported in previous studies conducted in India. Increase in the frequency and duration of quid chewing was associated with increased likelihood of developing these oral lichenoid lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 23 publications
(58 reference statements)
1
20
1
Order By: Relevance
“…[7] In their study, the individuals who quit the habit showed rapid resolution of the lesion, thereby, confirming the cause and effect hypothesis. [7] In a study conducted by Arya et al, [2] the prevalence of BQLL among quid chewers was 9.5% in contrast to that reported by Daftary et al [8] (0.7%). Furthermore, BQLL along with other quid-induced oral mucosal lesion (QOML) was more common in females when compared to males; though the basis for this is not known.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…[7] In their study, the individuals who quit the habit showed rapid resolution of the lesion, thereby, confirming the cause and effect hypothesis. [7] In a study conducted by Arya et al, [2] the prevalence of BQLL among quid chewers was 9.5% in contrast to that reported by Daftary et al [8] (0.7%). Furthermore, BQLL along with other quid-induced oral mucosal lesion (QOML) was more common in females when compared to males; though the basis for this is not known.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, BQLL along with other quid-induced oral mucosal lesion (QOML) was more common in females when compared to males; though the basis for this is not known. [2] For uniformity in the reporting of "betel quid" and tobacco chewing habits and associated oral mucosal lesions, a workshop was held in Kuala Lumpur, Malaysia, during November 25-27, 1996. [1] According to them, "quid" or any other type of chewing mixture should be described by listing out the specific ingredients to clearly outline the three basic categories mentioned below: 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations